Outcome of Patients Supported by Large Impella Systems After Re-implantation Due to Continued or Recurrent Need of Temporary Mechanical Circulatory Support - Sugimura, Yukiharu; Bauer, Sebastian; Immohr, Moritz Benjamin; Mehdiani, Arash; Rellecke, Philipp; Westenfeld, Ralf; Aubin, Hug; Boeken, Udo; Lichtenberg, Artur; Akhyari, Payam (Frontiers in Cardiovascular Medicine, 2022)
Despite growing utilization of large microaxial pump, i.e., Impella 5.0 or 5.5 (Abiomed Inc., Danvers, MA, USA) (Impella 5+) for cardiogenic shock (CS) patients, adverse events including the necessity of re-implantation have not been well discussed. In all 67 patients, in-hospital mortality was 52.2% (n=35). Explantation of Impella 5+ was performed in 39 patients (58.2%), 22 of whom (32.8%) recovered under Impella 5+, and ten further patients (14.9%) survived after a successful transition to permanent mechanical circulatory support. Embolic events were considerable complications in each access. They occurred at the right arm after removal of Impella 5+ via subclavian artery (SA) (n=3, 9.1%) or in the form of leg ischemia in patients with Impella 5+ via femoral artery (FA) (n=2, 33.3%). Re-implantation was necessary in 10 patients (14.9%) due to 1) recurrent CS (n=3), 2) pump thrombosis (n=5), or 3) pump dislocation (n=2), all of which were successfully performed via the same access route. In univariate analysis, FA access was a significant risk factor of pump dysfunction compared to SA access (FA vs. SA, 42.9% vs. 11.1%, p<0.05, odds ratio 6.75). Higher overall mortality but no statistical difference was observed in patients with re-implantation of Impella 5+ compared to patients with primary Impella 5+ support (re vs. primary, 80.0% vs. 47.4%, p=0.09). Our results suggest the acceptable clinical outcome of Impella 5+ despite a 15% re-implantation rate. Our observational data may merit further analysis of anticoagulation strategies including risk stratification for embolic events.